PREVALENSI CACING HATI SAPI PERAH PADA PETERNAKAN RAKYAT DI PROVINSI LAMPUNG - Siswanto Siswanto; Madi Hartono; Purnama Edy Santosa; Sri Suharyati; Hindun Larasati; Muhammad Mirandy Pratama Sirat (JURNAL ILMIAH PETERNAKAN TERPADU, 2018)
The study was conducted on dairy cattle livestock at Lampung Province in July - August 2012, aiming to determine the prevalence of liver worms. Disease in livestock caused by liver worm infections are called Fasciolosis. Fasciolosis is an important parasitic disease because it can cause high economic losses. The research method was the census method. Data retrieval were 125 dairy cattle faecal samples from people's dairy farms in Lampung Province. The datas obtained were analyzed descriptively. Examination of faecal samples was carried out at the Lampung Veterinary Center using the Sedimentation Test. The results showed the prevalence of liver worms in dairy cattle in Lampung Province was 12.00%, 15 dairy cattle those were positively infested by liver worms. The highest dairy cattle prevalence in West Lampung Regency at 33.33%, while the lowest prevalence is in dairy cattle in Bandar Lampung City and Tanggamus Regency at 0%. Keywords:  Dairy Cattle Livestock, Lampung Province, Liver Worms, Prevalence, Sedimentation Test